Two Cases of Iatrogenic Lumbar Foraminal Disc Herniations - Ryota Taniguchi; Osamu Kawano; Takeshi Maeda; Yasuharu Nakajima; Yuichiro Morishita (Case Reports in Orthopedics)
Study Design. A case report. Objective. We report two cases of iatrogenic deterioration of lumbar foraminal disc herniations following lumbar disc injections. Summary of Background Data. Complications associated with discography were reported. However, only a few reports have thus far referred to the iatrogenic deterioration of lumbar foraminal disc herniations. Cases. 60-year-old and 74-year-old men were treated with MR images of L4-5 foraminal disc herniations without fragment in the spinal canal. The patients underwent discography and disc block for its diagnosis and treatment. After disc injections, both patients complained of deterioration of L4 radiculopathy. Results. On disco-CT or reexamined MR images after disc injections, herniated fragment was migrated from neural foramen to cranial central spinal canal with was not shown in previous MR images. The herniated fragments were extirpated by means of osteoplastic laminoplasty or transforaminal lumbar interbody fusion with facetectomy. The herniated fragments were migrated from neural foramen to cranial central spinal canal. Conclusions. The injection of liquid medicine into the nucleus led the intradiscal pressure increased, and the disc fragment might prolapsed through the raptured region of annulus fibrosus and migrated to cranial central spinal canal by anatomical reason. The disc injection may have a risk for deterioration of foraminal disc herniation. Our report is instructive for the management of discography for the diagnosis of foraminal disc herniations.